Visual and Proprioceptive Perceptions Evoke Motion-Sound Symbolism: Different Acceleration Profiles Are Associated With Different Types of Consonants - Shinohara, Kazuko; Kawahara, Shigeto; Tanaka, Hideyuki (Frontiers in Psychology, 2020)
A growing body of literature has shown that one perceptual modality can be systematically associated with sensation in another. However, the cross-modal relationship between linguistic sounds and motions (i.e., motion-sound symbolism) is an extremely understudied area of research. Against this background, this paper examines the cross-modal correspondences between categories of consonants on one hand and different acceleration profiles of motion stimuli on the other. In the two experiments that we conducted, we mechanically manipulated the acceleration profiles of the stimuli while holding the trajectory paths constant, thus distinguishing the effect of acceleration profiles from that of motion path shapes. The results show that different acceleration profiles can be associated with different types of consonants; in particular, movements with acceleration and deceleration tend to be associated with a class of sounds called obstruents, whereas movements without much acceleration tend to be associated with a class of sounds called sonorants. Moreover, the current experiments show that this sort of cross-modal correspondence arises even when the stimuli are not presented visually, namely, when the participants’ hands were moved passively by a manipulandum. In conclusion, the present study adds an additional piece of evidence demonstrating that bodily action-based information, i.e., proprioception as a very feasible candidate, could lead to sound symbolic patterns.